Maus : a survivor's tale [book club bag] - Spiegelman, Art (Random House, 1997)
Maus is a haunting tale within a tale. Vladek's harrowing story of survival is woven into the author's account of his tortured relationship with his aging father. Against the backdrop of guilt brought by survival, they stage a normal life of small arguments and unhappy visits.